Milk Street vegetables : 250 bold, simple recipes for every season - Kimball, Christopher; Hirsch, J. M.; Locke, Michelle; Card, Matthew; Unger, Diane (Little, Brown and Company, 2021)
Chili-spiked carrots. Skillet-charred Brussels sprouts. Mashed potatoes brightened with harissa and pistachios. These are just three ways to put vegetables in the centre of your plate. With 250 recipes, the possibilities are nearly endless: a head of cauliflower can become Cauliflower Shawarma; Smothered Cauliflower with Tomatoes, Capers and Raisins; Sichuan Dry-Fried Cauliflower; Pasta with Cauliflower and Toasted Breadcrumbs; Cauliflower-Chickpea Salad with Dill-Lemon Dressing; or Curried Cauliflower Rice with Peas and Cashews.